ANALYSIS OF PHYTO-PATHOGENIC CONDITION OF MEDICINAL PLANTS AND PROSPECTS OF USING BIO-CONTROL IN PROTECTION SYSTEM - Pospielova, G. D.; Kovalenko, N. P.; Barabolya, O. V.; Zdor, V. M. (Scientific Progress & Innovations, 2020)
Medicinal plants are an important source of biologically active substances that are widely used in various in-dustries, especially pharmaceutical. Given the growing share of herbal medicines, the world's demand for herbal raw materials is increasing steadily. In medicinal crop production, the most important problem is the quality of grown products, and here a vulnerable part of the technology is damage to plants by diseases and pests. It neces-sitates the development of a certain system of protection. The most significant economic losses of medicinal raw materials are caused by powdery mildew and rust fungi, pathogens of root rot and spotting (phyllostictosis, ramu-lariosis, anthracnose, septoria disease, cercosporosis, and others). Their damaging plants leads to a decrease in the content of biologically active substances (essential oils, polysaccharides, flavonoids, and oxycinnamic acids, etc.). Seed infection has a significant impact on germination and development of plants, so phyto-examination of seeds for the presence of harmful micro-flora is an important element in the technology of growing medicinal plants. Analysis of scientific literature on phyto-pathogenic condition of medicinal plantations indicates the need to find new approaches to their protection against pathogens, which will improve the quality of medicinal plant raw materials. The systematic review of the data on the impact of biological products on the objects of target us-ing and objects of protection − medicinal plants − has shown the effectiveness of applying microorganisms in the fight against plant pathogens. Bio-fungicides have long been used to control the spreading and development of pathogens. Myco-parasitism, antibiosis and competitiveness for resources and space were considered the main control mechanisms. Recent studies show that their application initiates the induced systemic or local plant re-sistance. The vast majority of bio-fungicides contain fungi spores and mycelia (of Trichoderma ssp. strains) or spores and products of bacterial metabolism (Pseudomonas aureofaciens, P. fluorescens, and Bacillus subtilis). The preparations with various effect mechanisms are being actively studied in the system of biological protection of medicinal plants and include growth stimulants, immune modulators, and inducers of resistance. Due to strict requirements to the quality of medicinal plant raw materials, the variety of fungicides for the protection of medic-inal plants has decreased. Biological products are an alternative to them. However, their testing is carried out only on economically profitable crops (cereals, vegetables, and fruits) and a limited number of species of medici-nal plants. We consider it advisable to intensify research directed at bio-control of medicinal plants’ diseases.